Comprehensive Review of Prehospital Emergency Care: Enhancing Outcomes through Interdisciplinary Collaboration - Alshogaih, Mohammed Hadi Yahya; Almansour, Abdullah Hamad; Alyami, Ali Mahdi Ali; Almostneer, Ibrahim Mohammed Saleh; Alsulayyim, fahad Dhafer; AL Khamsan, Hussain Saleh Mohammed; Alyami, Salem Mahdi Mohammed; Alyami, Hussain Ahmed; Altheebh, Husien Ali Hussein; Alzuraya, Hadi Ali Hadi (Journal of Ecohumanism, 2024)
Prehospital emergency care is an indispensable link in consecutive emergency medical care, intended for initial stabilization and transport of patients in emergency conditions. All the services rendered by the different healthcare workers significantly guarantee the patient the best results when the sickness is severe or critical. Specifically, this review focuses on the importance of interdisciplinary teamwork in prehospital emergency care and assesses the effects of the cooperative work of paramedics, EMTs, nurses, physicians, and other stakeholders. The paper also reveals the difficulties in implementing effective teamwork in the prehospital care environment, including communication difficulties, lack of qualified training among the team members, and several practical concerns. Based on experiences, surveys, and research on quality practices, this paper discusses how multimodal communication influences patient outcomes, such as mortality probability, treatment effectiveness, and more. How training, protocols, and application of technology can be advanced to improve collaborative practice in prehospital emergency care is presented as the final recommendation of the review.